2011
DOI: 10.1103/physreve.84.031803
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of polymer adsorption to a flexible membrane

Abstract: We analyze the structural behavior of a single polymer chain grafted to an attractive, flexible surface. Our model is composed of a coarse-grained bead-and-spring polymer and a tethered membrane. By means of extensive parallel tempering Monte Carlo simulations it is shown that the system exhibits a rich phase behavior ranging from highly ordered, compact to extended random coil structures, and from desorbed to completely adsorbed or even partially embedded conformations. These findings are summarized in a pseu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Repression of MAPK signaling pathway has similar effects on the maintenance of PTEN, which revealed that the MAPK signaling pathway leads to the restoration of advanced breast cancers harboring PTEN loss [12]. Mitogenic-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathway has been found to play a role in some cancer therapies, as ERK1/2, one of MAPK/ERK kinases, was highly expressed in cervical cancer tissues [13], which also regulates many biological factors that affect types of miRNAs and their relevant machinery [14]. It has been indicated that some miRNAs, like miR-22, might have potential effects on cell biology via the regulation of PTEN expression [15].…”
Section: Original Researchmentioning
confidence: 99%
“…Repression of MAPK signaling pathway has similar effects on the maintenance of PTEN, which revealed that the MAPK signaling pathway leads to the restoration of advanced breast cancers harboring PTEN loss [12]. Mitogenic-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathway has been found to play a role in some cancer therapies, as ERK1/2, one of MAPK/ERK kinases, was highly expressed in cervical cancer tissues [13], which also regulates many biological factors that affect types of miRNAs and their relevant machinery [14]. It has been indicated that some miRNAs, like miR-22, might have potential effects on cell biology via the regulation of PTEN expression [15].…”
Section: Original Researchmentioning
confidence: 99%
“…Representative conformations that predominate in the different structural pseudophases labeled by a letter code adopted from Refs. [22][23][24][25] are compiled in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%
“…The problem considered in this paper could have practical implications for a broad variety of applications ranging from protein-ligand binding and designing smart sensors to molecular pattern recognition [9][10][11][12] and the discovery of new drugs that bind to specific receptors. Therefore, the theoretical treatment of the adsorption of macromolecules within the framework of minimalistic coarse-grained polymer models in statistical mechanics has been a long-standing problem [13,14] that still attracts a lot of interest [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has been dedicated to polymer adsorption on a family of finitely ramified fractals [31][32][33][34]. Also of great importance is the study of polymers in the vicinity of fluctuating surfaces, such as membranes [35,36]. In this concern, it is worthwhile to study the situation when the concentration of attractive sites on the surface is exactly at the percolation threshold and a spanning percolation cluster of attractive sites appears.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has been dedicated to polymer adsorption on a family of finitely ramified fractals [31][32][33][34]. Also of great importance is the study of polymers in the vicinity of fluctuating surfaces, such as membranes [35,36].…”
Section: Introductionmentioning
confidence: 99%